2020
DOI: 10.1149/ma2020-02141371mtgabs
|View full text |Cite
|
Sign up to set email alerts
|

Robustness of Ferroelectricity in Hafnium-Zirconium Dioxide Films Deposited By Sputtering and Chemical Solution Deposition for Ferroelectric Transistor Applications

Abstract: Since the discovery of ferroelectricity in HfO2 in 2011, extensive work begin to burst forth on HfO2-based ferroelectric materials and devices. Orthorhombic phase is responsible for ferroelectricity in HfO2, which is usually stabilized by the dopant such as Al, Zr, Si, la and Y. In particular, Zr doped HfO2 (HZO) has large Pr around 20 µC/cm2 and ferroelectricity can be obtained in a wide range of Zr composition. The orthorhombic phase is a metastable phase and Migita et al. [1] reported that the orthorhombic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…This indicates the ferroelectric properties of the sputtered HZO film crystallized at 1 atm were degraded by the re-annealing at as low as 400 °C. This is consistent with our previous works, 22,23) demonstrating that the XRD peak from the monoclinic phase in the sputtered HZO film, which had been crystallized at 1 atm of N 2 ambient, was increased by the re-annealing process and that the electrical properties were turned into paraelectric after re-annealing, although clear ferroelectric properties were observed before re-annealing. In addition, a similar observation was reported by Yajma et al They showed that degradation of ferroelectric properties due to the increase of monoclinic phase formation took place by the re-annealing or bake process even at as low as 250 °C for Ge-doped HfO 2 layer prepared by SFFB05-5…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…This indicates the ferroelectric properties of the sputtered HZO film crystallized at 1 atm were degraded by the re-annealing at as low as 400 °C. This is consistent with our previous works, 22,23) demonstrating that the XRD peak from the monoclinic phase in the sputtered HZO film, which had been crystallized at 1 atm of N 2 ambient, was increased by the re-annealing process and that the electrical properties were turned into paraelectric after re-annealing, although clear ferroelectric properties were observed before re-annealing. In addition, a similar observation was reported by Yajma et al They showed that degradation of ferroelectric properties due to the increase of monoclinic phase formation took place by the re-annealing or bake process even at as low as 250 °C for Ge-doped HfO 2 layer prepared by SFFB05-5…”
Section: Resultssupporting
confidence: 93%
“…In addition, we have recently reported that the sputtered HZO film became paraelectric after 400 °C, 15 min re-annealing in N 2 ambient, even though good ferroelectric properties had been initially observed. 22,23) This is fatal for some device applications. For example, when the bottom-gate structure ferroelectric gate thin film transistor is fabricated using an oxide semiconductor channel, a thin oxide semiconductor channel layer has to be deposited on the ferroelectric gate insulator, usually followed by the annealing process.…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary experimental results of Y-HZO films annealed in a vacuum and N 2 at 800 °C were presented in the FMA 37 conference extended abstract. 39) In this work, we investigated the ferroelectric properties of Y-HZO films annealed in a vacuum from 600-800 °C prepared by CSD. Later, Y-HZO films were annealed in vacuum, nitrogen and oxygen environments at 800 °C for comparative study.…”
Section: Introductionmentioning
confidence: 99%
“…However, we reported that the sputtered HZO film became paraelectric after 400 °C, 15 min of re-annealing in N 2 ambient, even though good ferroelectric properties were initially observed. 22,23) This is in contrast to the films prepared by chemical solution deposition (CSD), which has robust ferroelectricity after the reannealing process and even after the oxide channel layer formation at 600 °C. 24,25) One of the reasons for the discrepancy is that the CSD Y-HZO has more oxygen vacancies than the sputtered HZO.…”
Section: Introductionmentioning
confidence: 92%